ASSISTANCE IN REFORESTATION AND SOIL CONSERVATION TECHNIQUES AROUND THE MALIKUSSALEH UNIVERSITY REULEUT CAMPUS TOWARD A SUSTAINABLE ENVIRONMENT: PENDAMPINGAN REBOISASI DAN TEKNIK KONSERVASI TANAH DI SEKITAR KAMPUS UNIVERSITAS MALIKUSSALEH REULEUT MENUJU LINGKUNGAN YANG BERKELANJUTAN - Halim Akbar; Muhammad Authar; Muhammad Yusuf (WISDOM : Jurnal Pengabdian Kepada Masyarakat Wisdom, 2026)
The land surrounding the Universitas Malikussaleh Reuleut Campus is experiencing a decline in vegetation cover, increasing the potential for soil erosion. This condition requires sustainable conservation-based interventions. This community service program is designed as a pilot to create a green, sustainable campus environment. The program is implemented through mentoring, training, and field activities involving local communities, students, and village administrators. The mentoring activities include identifying critical land areas, planting adaptive local tree species, and applying soil conservation techniques such as biopore infiltration holes. The main objective of this program is to enhance community awareness and participation in environmental conservation efforts through reforestation and soil conservation techniques. The method adopted in this program utilises a participatory approach combined with adult learning principles (Participatory Training), encouraging active involvement from all participants. The expected outcomes of this program include establishing a campus-based collaborative model for environmental conservation, improving community understanding of soil conservation practices, and creating a greener, more productive, and sustainable environment around the campus.